SOCIODEMOGRAPHIC, BEHAVIORAL PROFILE AND SELF-PERCEPTION OF THE HEALTH CONDITION OF ADULTS OF THE FERRARIA DISTRICT, CAMPO LARGO, STATE OF PARANÁ, BRAZIL - Vanessa Moraes de Oliveira; Luzia Foltran de Azevedo Koch; Pablo Guilherme Caldarelli; Rafael Gomes Ditterich; Marcos Pascoal Pattussi; Marilisa Carneiro Leão Gabardo (Portal de Periódicos da Marinha do Brasil, 2021)
Our study aimed at tracing the sociodemographic, behavioral profile and self-perception of the health condition of adult residents of the Ferraria District, located in the municipality of Campo Largo, Paraná, Brazil. With a cross-sectional population-based design, a questionnaire was applied to residents, composed of socioeconomic data (social class, education, profession and income), demographic (sex, skin color, age and marital status) and behavioral (alcohol consumption, physical activity and morbidities), in addition to self-perception of health, housing and safety conditions. The data obtained were tabulated and expressed in frequencies. In total, 373 individuals were evaluated, with a mean age of 48.9 years. The most were women (73.2%) and white (63.5%), with incomplete middle school, and average family income of R$ 1,928.25. At the time of collection, 32.2% were unemployed. Regarding quality of life, 57.6% rated it as good. Among the health conditions and behavioral habits, the cases of hypertension stood out (42.0%) and cigarette smoke (70.0%). Regarding housing conditions, the most (n = 265; 76.0%) reported being "satisfied" and "very satisfied", while regarding safety during the day and at night, the answers focused on the category "sometimes", in both. We concluded that the profile of the sample analyzed is consistent with that of localities that have a certain degree of satisfaction, but that still lacks improvements in several aspects, such as those social, economic and infrastructure. Our study may be useful for directing actions of the organizations responsible for the most urgent demands of this community